Research Hotspots and Frontiers in Post Stroke Pain: A Bibliometric Analysis Study - Li, Chong; Shu, Xiaoyi; Liu, Xiangyun (Frontiers in Molecular Neuroscience, 2022)
Background: Pain is a common complication after stroke with a high incidence and mortality rates. Many studies in the field of pain after stroke have been published in various journals. However, bibliometric analysis in the domain of pain after stroke is still lacking. This study aims at delivering a visual analysis to analyze the global trends of research on the comorbidity of pain after stroke in the last 12 years. Methods: The publications from the Web of Science (WoS) in the last 12 years (from 2010 to 2021) were collected and retrieved. CiteSpace software was used to analyze the relationship of publication year with countries, institutions, journals, authors, references, and keywords. Results: A total of 322 publications were included in the analysis. A continuous but unstable growth in the number of papers published on pain after stroke was observed over the last 12 years. The Peoples' R China (65), Chang Gung University (10), and Topic in Stroke Rehabilitation (16) were the country, institution, and journal with the highest amount of publications, respectively. Analysis of keywords showed that shoulder pain after stroke and central post-stroke pain were the research development trends and focus in this research field. Conclusion: This study provides a visual analysis method for the trend and frontiers of pain research after stroke. In the future, large sample, randomized controlled trials are needed to identify the potential treatments and pathophysiology for pain after stroke